Mycobacterium tuberculosis Requires Cholesterol Oxidase to Disrupt TLR2 Signalling in Human Macrophages - Szulc-Kielbik, Izabela (Mediators Inflamm, 2019)
This study tested the hypothesis that Mycobacterium tuberculosis (Mtb) uses a cholesterol oxidase enzyme (ChoD) to suppress a toll-like receptor type 2- (TLR2-) dependent signalling pathway to modulate macrophages' immune response. We investigated the impact of Mtb possessing or lacking ChoD as well as TBChoD recombinant protein obtained from Mtb on the expression and activation of two key intracellular proteins involved in TLR2 signalling in human macrophages. Finally, the involvement of TLR2-related signalling proteins in an inflammatory/immunosuppressive response of macrophages to Mtb was evaluated. We demonstrate that wild-type Mtb but not the ∆choD mutant decreased the cytosolic IRAK4 and TRAF6 protein levels while strongly enhancing IRAK4 and TRAF6 mRNA levels in macrophages. Our data show that the TLR2 present on the surface of macrophages are involved in disturbing the signalling pathway by wild-type Mtb. Moreover, recombinant TBChoD effectively decreased the cytosolic level of TRAF6 and lowered the phosphorylation of IRAK4, which strongly confirm an involvement of cholesterol oxidase in affecting the TLR2-related pathway by Mtb. Wild-type Mtb induced an immunosuppressive response of macrophages in an IRAK4- and TRAF6-dependent manner as measured by interleukin 10 production. In conclusion, ChoD is a virulence factor that enables Mtb to disturb the TLR2-related signalling pathway in macrophages and modulate their response.